Third- and concerned-party positions in moral dilemmas: Effect of empathy on ethical judgment - Hiroshi Nonami; Shoji Ohtomo; Toshiaki Aoki; Motoaki Sugiura; Go Sakamoto; Kentaro Oba; Yutaka Tashiro (PLoS ONE, 2026)
The present study proposes a categorization of moral dilemmas into third-party dilemmas in which a judge’s choice affects only the life or death of others, and concerned-party dilemmas in which not only others’ but also the judge’s life or death is altered. While the former requires the judge to make only moral judgments to save others, another rational decision-making process that considers the judge’s life and death may also impact the latter. We examined ethical judgments based on these two types of dilemmas with a focus on empathic concern. Participants in Experiment 1 were more ethically permissive to save the many including him/herself at the expense of one person in the concerned-party dilemma than in the third-party dilemma, but empathic concern in both types of dilemmas consistently suppressed such utilitarian choices derived from “instrumental harm” (IH), which permits sacrificing a few necessary when it saves many. In Experiment 2, we also confirmed the suppressive effect of empathic concern for utilitarian choices derived from IH in the Pareto concerned-party dilemma in which the death of one person remains fixed regardless of the judge’s choice. We discuss the importance of categorizing these two types of dilemmas in moral dilemmas and demonstrates the public goods dilemma as a Pareto concerned-party dilemma in everyday life.